1991
DOI: 10.1136/hrt.66.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Silent ischaemia in diabetic men with autonomic neuropathy.

Abstract: Autonomic neuropathy is associated with an increased incidence of silent myocardial infarction and sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 13 publications
0
23
0
3
Order By: Relevance
“…In NIDDM patients the presence of autonomic neuropathy (AN) and reduced heart rate variability (HRV) have both been linked with a poor prognosis [4]. AN has also been associated with the presence of symptomatic CAD [5] and silent myocardial ischemia [6,7], which is a marker of CAD. tn IDDM patients the presence and degree of albuminuria has been linked to the presence of AN [8,9] and to the presence of silent myocardial ischemia and silent CAD [10].…”
Section: Introductionmentioning
confidence: 99%
“…In NIDDM patients the presence of autonomic neuropathy (AN) and reduced heart rate variability (HRV) have both been linked with a poor prognosis [4]. AN has also been associated with the presence of symptomatic CAD [5] and silent myocardial ischemia [6,7], which is a marker of CAD. tn IDDM patients the presence and degree of albuminuria has been linked to the presence of AN [8,9] and to the presence of silent myocardial ischemia and silent CAD [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are at least three studies which have shown that silent ischaemia is more prevalent in patients with autonomic neuropathy than in those with normal autonomic function [17,59,60] and two of these [59,60] show that the proportion of ischaemic episodes that are silent is higher in patients with autonomic neuropathy. Additional support for an association between autonomic neuropathy and silent myocardial ischaemia is provided by two studies [47,48] that found diabetic patients experienced chest pain later after the onset of ST depression than non-diabetic patients and this delay was related to impairment in the tests of autonomic nervous function.…”
Section: Association Of Diabetic Autonomic Neuropathy With Silent Myomentioning
confidence: 99%
“…Briefly, they consisted of measuring RR-interval variations during three tests using a computerized device (QMed, Laurence Harbor, NJ) (13). The Valsalva test, conducted with the patient seated, consisted of forcing exhalation and maintaining a pressure of 40 mmHg for 15 s. The result was expressed as the ratio of RR maximum to RR minimum.…”
Section: Other Cardiovascular Investigationsmentioning
confidence: 99%